2016
DOI: 10.1002/jsfa.7848
|View full text |Cite
|
Sign up to set email alerts
|

Health‐beneficial properties of potato and compounds of interest

Abstract: Potatoes have shown promising health-promoting properties in human cell culture, experimental animal and human clinical studies, including antioxidant, hypocholesterolemic, anti-inflammatory, antiobesity, anticancer and antidiabetic effects. Compounds present such as phenolics, fiber, starch and proteins as well as compounds considered antinutritional such as glycoalkaloids, lectins and proteinase inhibitors are believed to contribute to the health benefits of potatoes. However, epidemiological studies explori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 143 publications
(427 reference statements)
0
38
1
1
Order By: Relevance
“…However, the relevance of simple GI classification is discussed controversially in the literature. Variations in GI values can already be observed when considering different cultivars [57]. Thus, potatoes contain additional constituents that may affect the utilization of starch in the human organism, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevance of simple GI classification is discussed controversially in the literature. Variations in GI values can already be observed when considering different cultivars [57]. Thus, potatoes contain additional constituents that may affect the utilization of starch in the human organism, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, legume proteins are reported to be a rich source of hypotensive peptides with ACE-I inhibitory activity. 122 Compared to phenolic compounds, proteins and peptides are the main group of compounds shown to be implicated in the ACE-I inhibitory activity of several sources, including sea food, 123,124 meat and poultry, [125][126][127] egg, 128,129 milk and milk products, 130 potato, [131][132][133] legumes 134,135 and cereal grains. 130,136,137 Several studies have reported that protein hydrolysates exert a more potent ACE-I inhibitory activity than the unhydrolyzed protein.…”
Section: Functional Properties Ace Inhibitory Activitymentioning
confidence: 99%
“…152 Peptide fragments isolated from plant proteins are reported to exhibit their cholesterol-lowering properties by perturbing the intestinal absorption of dietary cholesterol and the enterohepatic bile acid circulation. Accordingly, this either disrupts cholesterol micelle formation, interferes with the cellular cholesterol carrier, or inhibits the lipogenic enzymatic activities and gene expression in hepatocytes and adipocytes 43,133,153,154 (Table 2). Prior to intestinal absorption, it is necessary for the dietary cholesterol to be incorporated into micelles along with phospholipids and bile salts.…”
Section: Hypocholesterolemic Activitymentioning
confidence: 99%
“…Bioactive compounds comprise nature-based ingredients such as nutraceuticals, peptides, antioxidants, with evidence of health-promoting effects via their activities on biological and physicochemical processes such as lipid metabolism control, energy expenditure [18,19]. In dietary experimental models [7,20,21], bioactive peptides from popular food crops, including soy and potato, have been studied for their anti-steatosis effects.…”
Section: Introductionmentioning
confidence: 99%